Boosting recovery before surgery: The impact of prehabilitation on upper gastrointestinal cancer patients - A quantitative comparative analysis. - Yuping Liu; Xiaoli Chen; Liqun Zou (PLoS ONE)
Background Emerging research presents divergent perspectives on the efficacy of prehabilitation for patients scheduled for surgery due to upper gastrointestinal (GI) cancers, capturing the attention of both the scientific community and surgical professionals. This quantitative comparative analysis seeks to assess the association of prehabilitation to ameliorate postoperative outcomes in individuals with upper GI cancers, thereby providing a comprehensive evaluation of its potential benefits within a surgical context. Materials and methods Medline, Embase, Cochrane Library and Web of Science were searched up to February 2024. Studies reporting the association between prehabilitation, and postoperative complications, readmissions or other outcomes of interest were included. Fixed or random effect models were used, and forest plots were applied to show the results of the quantitative comparative analysis. Results A total of 198 studies were initially screened based on titles and abstracts, with 129 studies subsequently excluded. Overall, 69 full-text studies were identified, of which 12 studies were finally included for qualitative analysis in the quantitative comparative analysis after determining whether the inclusion and exclusion criteria were met. The pooled results indicated that prehabilitation significantly reduced the overall postoperative complication rates in patients with upper GI cancer undergoing surgical therapy with the pooled OR of 0.59 (95%CI: 0.39-0.88). Moreover, prehabilitation was also shown to be a protective factor of pulmonary complications (OR: 0.54, 95%CI: 0.36-0.80) and ICU readmissions (OR: 0.23, 95%CI: 0.06-0.89). Conclusion The correlation between prehabilitation and a reduction in overall postoperative complications, pulmonary complications, and ICU readmissions among patients with upper GI cancer is substantiated by significant data. This pivotal finding necessitates further empirical investigation to validate these initial results and ascertain the clinical efficacy of prehabilitation protocols, thereby informing future surgical practice strategies.